Post-traumatic Growth Dimensions Differently Mediate the Relationship Between National Identity and Interpersonal Trust Among Young Adults: A Study on COVID-19 Crisis in Italy - Ellena, Adriano Mauro; Aresi, Giovanni; Marta, Elena; Pozzi, Maura (Frontiers in Psychology, 2021)
In Italy, The COVID-19 pandemic has caused a collective trauma. Posttraumatic growth (PTG) has been defined as the subjective experience of positive psychological changes as a result of a traumatic event. PTG can involve changes in five psychological main dimensions: relating to others, new possibilities, personal strength, spiritual change, and appreciation of life. In the context of national emergencies, those PTG dimensions encompassing changes at the social level (i.e., the relating to others dimension) can play a role in coping strategies that involve a renewed sense of self and one’s social identities, including national identities, and in turn, foster a stronger sense of trust and connection to others. Aim. To investigate how each of the five PTG dimensions mediates the association between the salience of national identity and interpersonal trust in a sample of Italian young adults. Trust in national and European institutions were expected to positively predict the strength of the Italian national identity which in turn was expected to be positively associated with interpersonal trust, and the PTG relating to others dimension to mediate this association. Method. This study involves the secondary analysis of data from a representative sample of 2,000 Italian young adults (age range 18–34 years). Participants completed a Web survey during the peak of the COVID-19 crisis in Italy with measures of trust in EU and national institutions, national identity, interpersonal trust and the PTG Inventory. Structural equation modeling procedures were employed for key hypotheses tests. Results. Trust in national institutions positively predicted national identity, which in turn was positively associated with interpersonal trust. Evidence of a full mediation effect of the PTG relating to others dimension on the association between national identity and interpersonal trust was found. Discussion. Findings contributes to clarify the psychological responses to collective traumas. In the context of Italy’s COVID-19 crisis, trust in national institutions reinforced Italian national identity, which was in turn associated with greater interpersonal trust, but only when psychological responses to the trauma involved changes in how individuals perceived and related to others, and not merely a focus on the self. Theoretical and practical implications are discussed.